Optimizing Time Performance in Implementing Green Building Concepts on High-Rise Residential by using M-Pert - Detty Kussumardianadewi, Bernadette; Eddy Husin, Albert; Septia Prawina, Riza (ASTONJADRO, 2024)
Climate change is a threat and crisis that is sweeping the world today, therefore the target towards Net Zero Emissions (NZE) by 2060 must be an obligation of all countries. The greenhouse effect, global warming, destruction of the ozone layer, destruction of forests, uncontrolled use of CFCs, and industrial disposal are factors that cause climate change. The consequences of climate change are dire, resulting in droughts, water scarcity, land fires, rising sea levels, flash floods, melting polar ice caps, storms, and biodiversity decline. Green buildings (GB) are important in saving energy, water, and other resources by meeting technical construction standards and applying green building principles with measurable performance. It is expected to reduce carbon emissions or greenhouse gases. From the results of research with the application of M-PERT, it is proven to be able to provide an accuracy of 98.93% implementation time in high-rise residential buildings